Implementasi Alat Penampung Air Hujan melalui Pendekatan Partisipatif di Desa Modelidu Kabupaten Gorontalo - Fitryane Lihawa; Achmad Nur Fahry Machmud; Ni Luh Julia Fera (Universitas Negeri Gorontalo, 2026)
This community service program supports Sustainable Development Goal (SDG) 6 by improving community access to alternative water resources through rainwater harvesting. The program aimed to implement an Appropriate Technology-Based Rainwater Harvesting System (RHS) in Modelidu Village, Telaga Biru District, Gorontalo Regency, using a participatory community empowerment approach. Activities were conducted over six weeks through community outreach, hands-on training, prototype construction, and post-installation assistance involving 50 community members. The implemented RHS prototype integrates a rooftop catchment system, a first-flush diverter, a multi-layer natural filtration unit, and a modular storage tank with a base capacity of 250 L that can be expanded to 1,000 L. Initial observations showed that the system achieved a rainwater collection efficiency of 70–80% and filtration performance up to 10 μm, while improving participants’ knowledge and practical skills in operating and maintaining the system. Harvested rainwater was utilized for non-potable domestic purposes, including washing and plant irrigation. The program demonstrates that integrating appropriate technology with participatory community empowerment provides an effective, affordable, and replicable solution for strengthening household water security in rural communities.